The Determinants of Paddy Fields Conversion in Java and Sumatra [Faktor-Faktor Penentu Konversi Luas Lahan Sawah di Jawa dan Sumatera] - Lusia Tri Harjanti; Yonosuke Hara (Pusat Penelitian, Badan Keahlian DPR RI, 2020)
Recently, the paddy fields conversion rate is alarmingly high and without significant effort by the government on the existing paddy fields, national food security and food self-sufficiency in Indonesia will be at risk. Therefore, to address this issue, the government needs to identify the main drivers of paddy fields conversion in Indonesia, particularly in Java and Sumatra as national rice barn. Employing panel data of 256 in the regencies/cities level in Java and Sumatra from 2010-2017, this study investigates the determinants of paddy fields conversion in Java and Sumatra. This study identified that the factors which affected paddy fields conversion in Java are the gross regional domestic product (GRDP) in agriculture sector, the GRDP in service sector, and population density. In contrary, the GRDP in service sector doesn’t significant with the changed of paddy fields in Sumatra, however GRDP in industry sector affect the paddy fields conversion in Sumatra. Other variables which affected paddy fields conversion in Sumatra are GRDP in agricultural sector and population density. Moreover, geospatial analysis also used in this study. It reveals that the changes of paddy fields in Java is dominated by settlement, and in Sumatra suspected turned dominated into palm oil plantation due to the growth of oil palm industry.Keywords: paddy fields, land conversion, geospatialAbstrakKonversi lahan sawah di Indonesia yang selalu meningkat setiap tahun bisa mengancam ketahanan pangan nasional dan swasembada pangan. Pemerintah perlu melakukan tindakan yang nyata dan signifikan untuk menanggulangi isu tersebut. Salah satu langkah awal untuk mengatasi permasalahan tersebut adalah dengan mengidentifikasi faktor-faktor pendorong konversi lahan sawah yang terjadi di Indonesia, terutama di Pulau Jawa dan Sumatera sebagai lumbung padi nasional. Oleh karena itu, dengan menggunakan data panel dari 256 kabupaten/kota di Pulau Jawa dan Sumatera pada periode tahun 2010-2017, penelitian ini menganalisa faktor-faktor penentu konversi lahan sawah di Jawa dan Sumatera. Hasil penelitian ini membuktikan bahwa faktor-faktor utama yang memengaruhi konversi lahan sawah di Jawa adalah PDRB di sektor pertanian, PDRB di sektor jasa, dan kepadatan penduduk. Sebaliknya, PDRB di sektor jasa tidak berpengaruh terhadap perubahan luas lahan sawah di Sumatera, melainkan PDRB di sektor industri memberikan dampak terhadap konversi lahan sawah di Sumatera. Faktor-faktor lain yang memengaruhi konversi lahan sawah di Sumatera adalah PDRB di sektor pertanian dan kepadatan penduduk. Analisis geospasial juga digunakan di dalam penelitian ini. Berdasarkan analisis geospasial, perubahan lahan sawah di Pulau Jawa didominasi menjadi area pemukiman, sedangkan sebagian besar perubahan sawah di Sumatera berubah menjadi area tanaman yang diduga adalah kelapa sawit. Kelapa sawit berkembang diduga karena pertumbuhan industri minyak kelapa sawit di Sumatera.Kata kunci: lahan sawah, konversi lahan, geospasial